2011
DOI: 10.22610/jebs.v3i6.289
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Risk Perception and Employee Investment Behavior

Abstract: Investment behavior of an investor depends on his/her risk perception and risk attitude. This paper attempts to explore that how the perception of an investor who is also the employee of that organization differs from other investors. Does he/she perceives risk similarly as other common investors or his relationship with the organization as an employee has any impact his/her risk perception, attitude and investment behavior. This research study is conceptual in nature and mainly based on previous literature fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Time horizon is defined as the time span over which an individual investor expects to hold the financial product that they have purchased (Shafi et al ., 2011, p. 347).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Time horizon is defined as the time span over which an individual investor expects to hold the financial product that they have purchased (Shafi et al ., 2011, p. 347).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The people who have experienced a hazardous situation may have less concern about risk [66]. There is a strong relationship between past experiences, risk perception, and decision-making [67]. However, differences between individual and group experiences could depend on the time-framework or the proximity to the hazard areas or with the peer-effect [65].…”
Section: Sociodemographic and Agri-hydrological Factorsmentioning
confidence: 99%
“…These studies throw more light on why professional and nonprofessional investors make investment decisions in the real world. However, a couple of studies attempted to explore the risk perception attitude of the investors but they left the exploration of link between risk perception and investment behavior of an employee of the company for future research (Shafi, Akram, Hussain, Sajjad & Rehman, 2011). Some studies found negative relationship between risk perception and investment decision.…”
Section: Introductionmentioning
confidence: 99%